Ranges of nutrient concentrations in Quercus ilex leaves at natural and urban sites - Maisto, Giulia; Baldantoni, Daniela; De Marco, Anna; Alfani, Anna; De Santo, Amalia Virzo (JOURNAL OF PLANT NUTRITION AND SOIL SCIENCE, 2013)
The leaf nutrient concentrations and the N-to-nutrient ratios were analyzed to evaluate the nutritional status of holm oaks (Quercus ilex L.) experiencing various anthropogenic pressures. Leaves (1 year old) of Q. ilex and surface soil (0-5cm) surrounding the trees were collected at seven natural and seven urban sites in Campania Region (Southern Italy) and analyzed for the concentrations of macro (C, N, P, S) and micronutrients (Mn, K, Na, Cu, Mg, Ca, Fe, Zn). The available soil fraction of micronutrients was also evaluated. The nutrients showed different concentration ranges for the natural and the urban sites in the soil (total and available) and in the leaves, that we reported separately. Organic-matter content and macronutrient concentrations were higher in the natural soils, while the highest leaf N, S, and P concentrations were found at some urban sites. Concentrations of Cu, Na and Zn both in leaves and soil, and Mg and Fe in leaves from the urban sites appeared to be affected by air depositions. Manganese was the only micronutrient to show higher concentrations at the natural than at the urban sites, both in soil and leaves. For this nutrient, in addition, a relationship between leaf and available soil concentrations was found at the natural sites. The ratios between the concentrations of N and each studied nutrient in the leaves highlighted a different nutritional status between the plants from the natural and urban sites.
Keywords: Campania Region; Holm oak; leaf N-to-nutrient ratios; southern italy; total and available soil nutrient concentrations